1998
DOI: 10.1074/jbc.273.12.6750
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of a GT Box (Sp1 Site) and Two Ets Binding Sites for Vascular Endothelial Cadherin Gene Transcription

Abstract: Vascular endothelial cadherin (VE cadherin) gene encodes a Ca2؉ -dependent cell adhesion molecule required for the organization of interendothelial junctions. This gene is exclusively and constitutively expressed in endothelial cells. Previous data with transgenic mice revealed that the transcriptional regulatory elements present within a ؊2486/؉24 DNA fragment of mouse VE cadherin gene mimic the tissue-specific activity of the endogenous promoter. In this study, we analyzed elements implicated in the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 37 publications
2
89
0
3
Order By: Relevance
“…Since the double EBS2/EBS4 mutant did not respond to Ets1 anymore, there must be no additional Ets1-responding sites left in the rest of the promoter. A previous study using a shorter version of the promoter had shown that EBS2 and EBS4 were necessary to the basal transcriptional activity of the promoter in endothelial cells, and that EBS4 was more e ective than EBS2 for this activity (Gory et al, 1998). Here, we suggest that Ets1 could be the Ets member that mediates these e ects: (i) EBS2 and EBS4 are necessary for transactivation by Ets1, (ii) transactivating activities of EBS2 and EBS4 are additive in response to Ets1, (ii) EBS4 is more responsive to Ets1 than EBS2, this latter e ect being probably due to its better binding to rEts1 than EBS2 (Figure 7a).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Since the double EBS2/EBS4 mutant did not respond to Ets1 anymore, there must be no additional Ets1-responding sites left in the rest of the promoter. A previous study using a shorter version of the promoter had shown that EBS2 and EBS4 were necessary to the basal transcriptional activity of the promoter in endothelial cells, and that EBS4 was more e ective than EBS2 for this activity (Gory et al, 1998). Here, we suggest that Ets1 could be the Ets member that mediates these e ects: (i) EBS2 and EBS4 are necessary for transactivation by Ets1, (ii) transactivating activities of EBS2 and EBS4 are additive in response to Ets1, (ii) EBS4 is more responsive to Ets1 than EBS2, this latter e ect being probably due to its better binding to rEts1 than EBS2 (Figure 7a).…”
Section: Discussionmentioning
confidence: 98%
“…This approach was chosen primarily because endothelial cells are notoriously refractory to transfection and our experiments validated this choice: the MFG retrovirus transduced the gene to the cells with more than 80% e ciency and the viral promoter provided signi®cantly higher expression levels of Ets1 transcripts and proteins in Figure 7 Binding of Ets1 to functional EBS in the VE-cadherin gene. (A) Recombinant Ets1 (rEts1, approximately 1 ng) was assayed for binding to 32 P-labeled double-stranded oligonucleotides (10 ng) corresponding to the various EBS present in the proximal region of the VE-cadherin gene (Gory et al, 1998) by electromobility-shift assay. The complexes formed by rEts1 and EBS2 or EBS4 were super-shifted by the addition of 250 ng of anti-Ets1 antibody (SS).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations